Estudio y valoración del espacio público en la ribera del río Cutuchi, de la ciudad de Latacunga - García Vilcacundo, Josselyn Belén (2022)
This investigation rises from the desire to know about the development of public areas on the riverbanks of the Cutuchi river concerning Latacunga city and its growth. This research aims to analyze the reality of the sector to determine appropriate urban and architectonic strategies that would improve the urban relationship of the city. A graphic study was performed to complete the above on the current state of the sector, the growth history, and different historical elements related to the area of study to objectively understand the problems to solve. The final product graphically summarizes different design strategies that would be executed as part of a proposal developed for the investigated sector. The proposed methods aim to solve the needs of the place